2012
DOI: 10.1098/rstb.2011.0344
|View full text |Cite
|
Sign up to set email alerts
|

Warming reduces the growth and diversity of biological soil crusts in a semi-arid environment: implications for ecosystem structure and functioning

Abstract: Biological soil crusts (BSCs) are key biotic components of dryland ecosystems worldwide that control many functional processes, including carbon and nitrogen cycling, soil stabilization and infiltration. Regardless of their ecological importance and prevalence in drylands, very few studies have explicitly evaluated how climate change will affect the structure and composition of BSCs, and the functioning of their constituents. Using a manipulative experiment conducted over 3 years in a semi-arid site from centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
137
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(149 citation statements)
references
References 91 publications
10
137
1
1
Order By: Relevance
“…Expected changes in temperature and rainfall frequency may even promote extreme mortality events, as recently recorded in organisms as disparate as small birds [63] and mosses [64]. Recent experimental studies have also shown that warming by 2-38C will reduce the cover and diversity of BSCforming lichens [65], and will promote declines in both bacterial and fungal activity and biomass, overall bacterial diversity and the bacteria:fungi ratio [64,66,67] in drylands.…”
Section: Global Environmental Change Effects On Drylandsmentioning
confidence: 95%
See 1 more Smart Citation
“…Expected changes in temperature and rainfall frequency may even promote extreme mortality events, as recently recorded in organisms as disparate as small birds [63] and mosses [64]. Recent experimental studies have also shown that warming by 2-38C will reduce the cover and diversity of BSCforming lichens [65], and will promote declines in both bacterial and fungal activity and biomass, overall bacterial diversity and the bacteria:fungi ratio [64,66,67] in drylands.…”
Section: Global Environmental Change Effects On Drylandsmentioning
confidence: 95%
“…Despite the multiple ecosystem processes and organisms affected by them, relatively few experimental studies have evaluated the response of BSC constituents to global change drivers, and most of them have been carried out in drylands from North America and Australia [64,[151][152][153][154]. Escolar et al [65] evaluated how the composition, structure and performance of lichen-dominated BSCs respond to predicted climatic changes in semi-arid, central Spain. Warming according to the Intergovernmental Panel for Climate Change projections [25] promoted a significant decrease in the richness and diversity of the whole BSC community, a result that was accompanied by important shifts in species composition.…”
Section: Research Gaps and Future Directionsmentioning
confidence: 99%
“…Alarmingly, some experimental work suggests biocrust communities may also be highly sensitive to changing climate. Specifically, increased temperatures have been reported to reduce lichen cover in semiarid Spain (12,34), and altered precipitation patterns promoted rapid moss mortality (35) and greater variability in cyanobacterial species composition and abundance (36,37) in a cool desert of the Colorado Plateau. These changes in biocrusts due to climate manipulations also impact ecosystem processes (12,35,38).…”
mentioning
confidence: 99%
“…Despite concern over potential climate change-induced shifts in biocrust community structure and the impacts on ecosystem processes, available reports of biocrust responses to climate manipulations are based on relatively short experimental time spans, often less than 3 y in duration (e.g., 12,[34][35][36]39). In addition to the lack of long-term data on biocrust responses to climate change, it is not yet known how climate change impacts on biocrust communities will compare with large, continued…”
mentioning
confidence: 99%
“…It is essential that such rangeland monitoring tools recognize the need to integrate the important local institutional factors we have identified to enable practical advice to be given on land management decisionmaking. The development of such approaches needs to incorporate scientific advances [120,121] related to understanding carbon storage and ecological processes into rangeland monitoring tools that can initially be used by PES project staff. These approaches will then require extension to enable pastoralist communities to be involved in monitoring carbon-storage changes and the associated (costs and) benefits that accrue from changes in land-management practices.…”
Section: Challenges For Cb-pes Projects In Rangelandsmentioning
confidence: 99%